'She would work out how she was going to live': Widowhood in Colm Tóibín's Nora Webster. Issue 2 (November 2018) - Carregal-Romero, José
Abstract : Set in 1960 and 1970s Enniscorthy, Colm Tóibín's Nora Webster is narrated from the perspective of the recently widowed mother, Nora, who has to deal with bereavement, heed her two young sons and acquire a new familial role as a breadwinner while keeping all her responsibilities as a mother. This article contemplates the ways in which the socio-cultural construction of widowhood hampers the protagonist's progression towards a renewed sense of self, away from a grief-based identity as a widow. As shall be explained, Nora Webster requires to be read in light of the social expectations attached to traditional norms of grief and the expectations of widowhood in patriarchal Ireland.